1979
DOI: 10.1063/1.438254
|View full text |Cite
|
Sign up to set email alerts
|

Variable angle photoelectron spectroscopy of the fluoroethylenes

Abstract: He I photoelectron spectra of fluoroethylene, 1,1-difluoroethylene, cis-1,2-difluoroethylene, trans-1,2-difluoroethylene, trifluoroethylene, and perfluoroethylene were obtained over the scattering angle range of 45' to 120' and compared with those of ethylene. Vibrational frequencies of the ionic states were measured and their symmetry modes assigned. The asymmetry parameter /3 as a function of the ionization potential was measured for each molecule. The value of /3 for the first ionization potential band of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 70 publications
5
26
0
Order By: Relevance
“…18 Ab initio calculations suggest that all four molecules remain planar upon ionization, but when Franck-Condon factors are considered, loss of planarity is discovered for 1,1-C 2 H 2 F 2 as a result of ionization from the C=C double bond. The successful application of fitting the ground state band with the Franck-Condon intensities and apparent similarities between the PES 1,3,5,6 and TPES of this work indicates that no autoionization effects are seen. Locht et al 5,6 reported a large intensity ratio for the excited vs. ground electronic state bands in the TPES, whereas we find that the ground state bands have comparable intensities to the first excited state band in the TPES.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…18 Ab initio calculations suggest that all four molecules remain planar upon ionization, but when Franck-Condon factors are considered, loss of planarity is discovered for 1,1-C 2 H 2 F 2 as a result of ionization from the C=C double bond. The successful application of fitting the ground state band with the Franck-Condon intensities and apparent similarities between the PES 1,3,5,6 and TPES of this work indicates that no autoionization effects are seen. Locht et al 5,6 reported a large intensity ratio for the excited vs. ground electronic state bands in the TPES, whereas we find that the ground state bands have comparable intensities to the first excited state band in the TPES.…”
Section: Introductionmentioning
confidence: 87%
“…Although some vibrational structure has been observed in the ground-state PE band by others, 1,3 this is the first high resolution TPES of this molecule reported in the literature. The (4a ) 2 HOMO of the neutral C S C 2 HF 3 molecule has C=C π orbital character, and the cation electronic ground state has the term symbolX 2 A .…”
Section: Trifluoroethenementioning
confidence: 99%
See 3 more Smart Citations